Activating the pseudocapacitance of multiple-doped carbon foam via long-term charge-discharge circulation. (16th January 2023) - Lu, Fei; Kong, Weijie; Su, Kun; Xia, Peng; Xue, Yanming; Zeng, Xianghua; Wang, Xi; Zhou, Min
Graphical abstract: A triple doping strategy was employed to fabricate boron, nitrogen, and oxygen doped graphite foam (BNO-GF). The BNO-GF delivered a favorable initial specific capacitance, and further dramatically boosted the pseudocapacitance without sacrificing long-term stability. Highlights: A facile triple doping strategy is employed to fabricate boron, nitrogen, and oxygen co-doped graphite foam (BNO-GF). The charge-discharge circulation triggers the amplification of the disorder of BNO-GF, thus boosting the pseudocapacitance by a factor of 1.9. The dynamic equilibrium between microscopic disordering and macroscopic framework maintenance of BNO-GF enables the long-time dynamic stability. Abstract: Carbon-based supercapacitors, featuring superior power density and stability, are strongly desired for electrical vehicles, yet suffered from their low energy densities. Recently, incorporating pseudo-capacitive constituents into the carbon matrix has been emerged as a prevailing method to increase its capacitance, while usually accompanied with declined stability. Herein, we employed a triple doping strategy to fabricate boron, nitrogen, and oxygen co-doped graphite foam (BNO-GF). The multiple dopants trigger a favorable initial specific capacitance of BNO-GF. Interestingly, the specific capacitance of the BNO-GF increases along with the charge-discharge circulation. An enhancement of the capacitance (∼40 %), entirely the pseudocapacitance, was further determined. Detailed structural characterization further determines a merging of the defective domains during cycles. With an amplifying disordering, these merged defective domains contribute a boosted pseudocapacitance. Meanwhile, the carbon framework maintains the structural integrity, without scarifying stability. This work provides a novel route to activate the carbon materials towards superior pseudocapacitance.